Interleukin-28A maintains the intestinal epithelial barrier function through regulation of claudin-1 - Li, Liangzi (Ann Transl Med, 2021)
BACKGROUND: Interleukin-28A (IL-28A or interferon-λ2) is reported to maintain intestinal mucosal homeostasis. However, the effects and mechanisms of IL-28A on intestinal ischemia reperfusion (I/R) have not yet been studied. METHODS: Adult C57BL/6 mice were randomly divided into three groups: sham, I/R, and I/R+IL-28A (n=5 in each group). The I/R+IL-28A group mice were injected with recombinant mouse IL-28A 12 hours before the operation. Mice were sacrificed 6 hours after reperfusion. The mucosal permeability was investigated, and histology analyses were performed. Additionally, a hypoxic Caco-2 cell culture model was established. Fludarabine was used to inhibit phosphorylated signal transducer and activator of transcription 1 (pSTAT1). The expression of IL-28A, tight junctions (TJs), and pSTAT1 was assessed by western blot, immunohistochemical (IHC) staining, or immunofluorescence staining. Epithelial permeability was measured by transepithelial electrical resistance (TER). RESULTS: The expression of IL-28A was decreased in intestinal lamina propria in the I/R group compared with the control group. Administration of IL-28A significantly alleviated the I/R-induced increase in intestinal permeability and tissue damage. Treatment with IL-28A significantly attenuated intestinal I/R-induced disruption of TJ proteins, including zonula occludens-1 (ZO-1), occludin, and claudin-1. In vitro, IL-28A treatment reversed the decrease in TER of Caco-2 monolayers exposed to hypoxic environments. IL-28A led to the activation of STAT1 and the upregulation of claudin-1 expression both in vivo and in vitro. Also, inhibiting phosphorylation of STAT1 reversed the effects of IL-28A on the expression and distribution of claudin-1 in Caco-2 cells. CONCLUSIONS: Intestinal epithelial barrier dysfunction caused by intestinal I/R is ameliorated by IL-28A via the regulation of claudin-1.